The Impact of Remittances and Financial Development on Income Inequality: Evidence from Low- and Middle-Income Economies Using a Dynamic Panel Threshold - Mili, Hela; Tarchoun, Monaem (Journal of Ecohumanism, 2025)
This article studies the connection between income inequality, financial development, and remittances for a sample of low- and middle-income nations. Few studies have examined how remittances and financial development simultaneously affect inequality; much of the research that has been done in this area focuses on the relationship between remittances and inequality or the relationship between financial development and inequality. The combined effect of these two on inequality has not, however, been explored in any of the recent studies. We add to the literature in a number of ways. The study used an econometric panel threshold with macroeconomic data during the period 1990 to 2020. We analysed whether remittances and financial development work in conjunction or as a substitution for to reduce inequality. We discovered evidence that, in nations with higher levels of inequality, remittances substitute financial development. However, in nations with less severe inequality, remittances complement financial development to reduce inequality. Second, we found that the impact of remittances on substitution is greater than their complementing effect. Finally, we found that financial development and remittances have various effects because of the conditional distribution of disparities, even though prior research has claimed that these two factors have homogenous effects on inequalities